2013
DOI: 10.1083/jcb.201304133
|View full text |Cite
|
Sign up to set email alerts
|

The GEF Bcr activates RhoA/MAL signaling to promote keratinocyte differentiation via desmoglein-1

Abstract: The GEF Bcr promotes RhoA-dependent actin remodeling and MAL/SRF signaling in keratinocytes, which in turn promotes differentiation via regulation of desmoglein-1 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 75 publications
(107 reference statements)
2
25
0
Order By: Relevance
“…In addition, the receptor tyrosine kinase EphA2, in a ligand-dependent manner, promotes entry of keratinocytes into a terminal differentiation pathway through a mechanism reliant on Dsg1 (Lin et al 2010). Finally, the RhoA GEF breakpoint cluster region (Bcr) has been shown to promote keratinocyte differentiation through the regulation of MAL/SRF signaling, again in a manner that is dependent on Dsg1 (Dubash et al 2013). …”
Section: Desmosomal Cadherinsmentioning
confidence: 99%
“…In addition, the receptor tyrosine kinase EphA2, in a ligand-dependent manner, promotes entry of keratinocytes into a terminal differentiation pathway through a mechanism reliant on Dsg1 (Lin et al 2010). Finally, the RhoA GEF breakpoint cluster region (Bcr) has been shown to promote keratinocyte differentiation through the regulation of MAL/SRF signaling, again in a manner that is dependent on Dsg1 (Dubash et al 2013). …”
Section: Desmosomal Cadherinsmentioning
confidence: 99%
“…Suppression of PKC-a or PKC-d isoforms increases Dsg3 expression, whereas suppression of PKC-d and PKC-1 isoforms either decreases or increases Dsg1 levels, respectively (Szegedi et al 2009 (Roemer 2012) and p63 has been shown by chromatin immunoprecipitation (ChIP) to bind and activate Dsg1, Dsc3, and Dp promoters (Ferone et al 2013;Johnson et al 2014). Rho-mediated changes in the actin cytoskeleton lead to changes in Srf-dependent transcription (Miralles et al 2003) and Srf controls the expression of Pkp2 and Dsg1, which in turn drives a program of terminal differentiation (Leitner et al 2011;Dubash et al 2013), The Wnt-regulated TCF/Lef transcription complex has been implicated in regulation of Dsg4, Dsc2, Dsc3, and Pg expression but direct binding of these transcription factors to desmosomal component promoters has only been shown in a few instances (Table 1) (Bazzi et al 2009;Bailey et al 2012;Tokonzaba et al 2013). Pg itself complexes with TCF/ Lef-1 to regulate the balance of Dsc2 and Dsc3 expression (Tokonzaba et al 2013).…”
Section: Transcriptional Regulation Of Desmosomal Componentsmentioning
confidence: 99%
“…DSG1 is a transmembrane glycoprotein. It is involved in regulating keratinocyte differentiation , epidermal differentiation and morphogenesis .…”
Section: Resultsmentioning
confidence: 99%